Factors influencing the intention to purchase health insurance: a study of Indian tobacco and alcohol consumers - Mishra, Ashok; Jamshed, Mohammed; Ahmad, Asad; Garg, Swati; Madsen, Dag Øivind (Frontiers in Public Health, 2024)
In this study, we empirically investigate the attitudes of tobacco and alcohol consumers toward health insurance purchases in India. We propose an extended theory of planned behavior (TPB) model comprising factors like attitude, subjective norms, perceived behavior control, perceived usefulness, perceived product risk, and intention to purchase. The study aims to determine the factors playing a significant role in determining the purchase intention of health insurance among tobacco and alcohol consumers. We collected responses from 420 tobacco and alcohol consumers through a Google Forms link shared via different social media platforms. SPSS has been used to perform exploratory factor analysis, whereas AMOS has been used to validate the constructs, confirm the relationships among the variables, and analyze the data. The analysis outcomes demonstrate that subjective norms, perceived product risk, and perceived behavioral control are the factors that have a positive and significant effect on health insurance purchase intention among consumers. These factors are the ones that the insurance industry should keep in mind when developing policies for the growth of the health insurance sector.